2020
DOI: 10.1093/asj/sjz319
|View full text |Cite
|
Sign up to set email alerts
|

Full-Field Erbium:YAG Laser Resurfacing: Complications and Suggested Safety Parameters

Abstract: Background Laser skin resurfacing with erbium-doped yttrium aluminum garnet (Er:YAG) lasers is a newer alternative to CO2 laser treatment, and was developed to reduce common complications. Although Er:YAG lasers have been available for years, safety parameters for efficacious resurfacing with these devices have not previously been available. Objectives The aim of this study was to utilize one practice’s laser treatment settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“… AEs observed in this study compared with similar AEs in two recent facial skin resurfacing studies including HPDR (lower energy, single pass treatment; Holcomb et al) and dual mode erbium YAG laser skin resurfacing (Weniger et al 23 ). a Number of patients determined based on percentage observed and total patients treated.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“… AEs observed in this study compared with similar AEs in two recent facial skin resurfacing studies including HPDR (lower energy, single pass treatment; Holcomb et al) and dual mode erbium YAG laser skin resurfacing (Weniger et al 23 ). a Number of patients determined based on percentage observed and total patients treated.…”
Section: Discussionsupporting
confidence: 74%
“…No new AEs unique to this technology were identified—all AE types recorded in this study have also been observed with other full-field facial skin resurfacing treatments including nitrogen plasma skin regeneration and laser skin resurfacing (CO 2 and Erbium YAG). 20-22 Similar AEs were observed in a recent clinical study using the updated helium plasma device wherein only a single pass at a lower power setting (20%) was performed 13 ; more severe AEs were observed in a recent clinical study using the Erbium YAG laser for deep resurfacing 23 (see comparison of AEs; Table 3 ).…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations